IMPLEMENTASI SISTEM INFORMASI GEOGRAFIS (SIG) PADA MANAJEMEN RUTE PENGIRIMAN BARANG - Ramadhan; Joko Suwarno (JUPIK : Jurnal Penelitian Ilmu komputer, 2025)
The implementation of Geographic Information System (GIS) has great potential to enhance the management of delivery routes for goods by providing a streamlined and efficient system. GIS allows real-time route visualization, accurate distance calculation, and route optimization using advanced algorithms such as Dijkstra's Algorithm. These capabilities help reduce delivery time, transportation costs, and operational inefficiencies. Despite these benefits, many logistics companies have not maximized the utilization of GIS technology. This leads to longer delivery times, higher transportation costs and centralized management. This study aims to design and implement a GIS-based system for managing delivery routes, focusing on route optimization, real-time monitoring, and centralized data management. The system integrates web and Android platforms, providing real-time tracking through GPS to ensure the timely and safe delivery of goods. The findings are expected to benefit researchers by contributing to the understanding of GIS applications and Dijkstra's Algorithm in logistics. For companies, the implementation of this system could optimize delivery routes, reduce costs, and improve customer satisfaction. Additionally, it provides a valuable reference for future research and development in the logistics sector